Exploring proinsulin proteostasis: insights into beta cell health and diabetes - Zavarzadeh, Parisima Ghaffarian; Panchal, Kathigna; Bishop, Dylan; Gilbert, Elizabeth; Trivedi, Mahi; Kee, Tovaria; Ranganathan, Srivastav; Arunagiri, Anoop (Frontiers in Molecular Biosciences, 2025)
Proinsulin misfolding is central to diabetes. This review examines the cellular mechanisms regulating proinsulin proteostasis in pancreatic β-cells, encompassing genetic factors such as insulin gene mutations, and exploring the roles of endoplasmic reticulum (ER) stress and the unfolded protein response (UPR), ER redox balance, mitochondrial function, and the influence of extrinsic factors. Mutations in the INS gene, particularly those affecting cysteine residues, impair folding and disulfide bond formation, often exhibiting dominant-negative effects on the wild-type proinsulin. The importance of ER quality control mechanisms, including chaperones and oxidoreductases, in facilitating proper folding and degradation of misfolded proinsulin is emphasized. Disruptions in these systems, due to genetic mutations, ER stress, or impaired ER-to-Golgi trafficking, lead to proinsulin accumulation and β-cell dysfunction. The unfolded protein response (UPR), especially the PERK and IRE1α-XBP1 pathways, emerges as a central regulator of protein synthesis and ER stress management. The review also discusses the role of mitochondrial health, ER redox state, and extrinsic factors such as diet and medications in influencing proinsulin proteostasis. Finally, the structural insights from NMR and molecular dynamics simulations are discussedhighlighting the dynamics of misfolding and underscoring the importance of disulfide bonds. These mechanistic insights suggest innovative strategies targeting thiol/disulfide redox systems in cells to mitigate protein misfolding diseases including diabetes.